Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 4 - Polynomials - 4.6 Special Products - 4.6 Exercise Set - Page 278: 107



Work Step by Step

Use the formula $(a+b)(a-b)$ to multiply the last 2 factors to obtain: $=(4x^2+9)[(2x)^2-3^2] \\=(4x^2+9)(4x^2-9)$ Use the same formula again with $a=4x^2$ and $b=9$ to obtain: $=(4x^2)^2-9^2 \\=16x^4-81$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.